PEMBERIAN TEPUNG DAUN SIRIH (Piper Betle L.) PADA SAPI PERAH LAKTASI PASCA PUNCAK PRODUKSI UNTUK MENGOBATI DAN MENCEGAH MASTITIS SUBKLINIS - Asep Sudarman; Dedy Supriadin; Anuraga Jayanegara (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
The objective of the experiment was to find the best administration method of betel leaf meal in long term to prevent and to treat subclinical mastitis of lactating dairy cows. The experimental design used was a completely randomized design with four treatments and three replications and used twelve cows. The treatments were P0 (without betel leaf meal, as control), P1 (administration of betel leaf meal every day), P2 (administration of betel leaf meal with one week interval) and P3 (administration of betel leaf meal in 3 weeks and 1 week off). Parameters measured were somatic cell count, milk composition, milk production, immunoglobulin (IgG), level of glucose and triglyceride. Data were analyzed by using analysis of variance (ANOVA) and the differences amongst treatments were examined by Duncan multiple range test. Results showed that number of somatic cells in the control (P0) increased by 17.22%, whereas P1, P2 and P3 decreased somatic cell count by 95.74, 97.17 and 89.03%, respectively. Supplementation of betel leaves did not significantly affect milk composition, IgG, glucose and triglyceride. It was concluded that supplementation of betel leaf meal with one week interval (P2) was the best method in lowering the number of somatic cells and increasing milk production without changing the composition of milk.